Rank-based content updating method in FemtoCaching - Apipong Pingyod (2018)
© 2014 IEEE. In the FemtoCaching research, an approximation algorithm to place contents in the cache of femto-cells is proposed. However, this research does not consider changes of content ranking and content popularities that change during time. Hence, contents in femto-cells should be updated with limited number of updated contents. There is a popularity-based updating method that replaces low popularity contents by high popularity contents but its performance is not good in case of high limited threshold. This problem occurs because diversity of contents in distributed caches is decreased. Hence, we propose a new method in this paper called rank-based updating method that attempts to cache diverse contents in distributed caches. It updates contents in femto-cells by considering ranking number of each content in ranking with the same ranking number of each content in femto-cells. A complexity of the proposed method is lower than the algorithm of FemtoCaching and slightly more than the popularity-based updating method. Performance of the proposed method is evaluated by simulation. Experimental results show that the performances of the proposed method are almost the same as the limited FemtoCaching method and better than the popularity-based updating method in case of high limited threshold.